Synthesis and evaluation of novel 2, 4-disubstituted arylthiazoles against T. brucei. Issue 1 (19th December 2019) - Georgiadis, Markos-Orestis; Kourbeli, Violeta; Papanastasiou, Ioannis P.; Tsotinis, Andrew; Taylor, Martin C.; Kelly, John M.
Abstract : 2-2-[3-(1-Adamantyl)-4-fluorophenyl]thiazol-4-ylethan-1-amine (1a ) and 2-2-[4-(1-adamantyl)phenyl]thiazol-4-ylethan-1-amine (2a ) exhibit activity against T. brucei in the range of IC50 = 0.42 μM and IC50 = 0.80 μM, respectively. Abstract : The design, synthesis and pharmacological evaluation of the 4-substituted-2-[3-(adamant-1-yl)-4-fluorophenyl]thiazoles 1a–j, the 4-substituted-2-[4-(adamant-1-yl)phenyl]thiazoles 2a–h, the 2-substituted-4-[4-(adamant-1-yl)phenyl]thiazoles 3a–e, the N -substituted 2-phenylthiazol-4-ethylamides 4a, b and the N -substituted 4-phenylthiazol-2-ethylamides 4c, d is described. Compounds 1a and 2a exhibit trypanocidal activity in the range of IC50 = 0.42 μM and IC50 = 0.80 μM, respectively. Both of these derivatives bear a lipophilic end, which consists of a 4-(1-adamantyl) phenyl or a 3-(1-adamantyl)phenyl moiety, a 1, 3-thiazole ring and a functional end, which comprises of an alkylamine and can be considered as promising candidates for the treatment of Trypanosoma brucei infections.